Assessment of Different Properties of Lightweight Concrete using Expanded Polystyrene Beads Extracted from Thermocol Wastage - Gyawali, Tek Raj (Himalayan Journal of Applied Science and Engineering, 2022)
Nepal is facing the problem of thermocol wastage, especially in the damping site nearby the urban areas. The thermocol wastage were crushed by a hammer and the extracted expanded polystyrene (EPS) beads was used as aggregates to produce the lightweight concrete. The content of EPS beads was 0, 20, 30, 40, 50, and 60 % by the total volume. Mechanical properties like density, different strengths, and Young’s modulus were experimentally evaluated on ranging percentages of EPS. The 28-day compressive, flexural, splitting tensile strengths and Young’s modulus of the control mixture were 59.9 MPa, 5.21 MPa, 4.43 MPa, and 20898 MPa respectively. The decrease on compressive strength was by 62 %, 72 %, 81 %, 88 %, and 93 % respectively for 20 %, 30 %, 40 %, 50 %, and 60 % EPS content respectively. It was 26 %, 41 %, 51 %, 57 %, and 69 % for flexural strength, 46 %, 60 %, 70 %, 80 %, and 88 % for the splitting tensile strength and 45 %, 56 %, 61 %, 70 %, and 77 % for Young’s modulus respectively. Drying shrinkage, freezing and thawing, and water absorption tests were conducted to evaluate the durability of EPS concrete. All properties were compared with the auto-cleaved lightweight concrete (ALC). It revealed that the EPS beads extracted from the thermocol wastage can be re-used to produce the structural and non-structural concrete depending on its percentages. It can easily solve the never-decomposing problems of thermocol wastage. Moreover, ALC can be replaced by EPS concrete for the in-fill and partition walls of the buildings.